Novel ultrasound features and diagnostic clues of gastric-type endocervical adenocarcinoma: a case series - Yang, Liwen; Wang, Yangyang; Cai, Jian; Xiong, Ying; Li, Juan; Zhou, Qi; Ye, Nan; Lai, Hua; Liu, Tianjiao; Zhou, Liuying (Frontiers in Oncology, 2025)
BackgroundGastric-type endocervical adenocarcinoma (G-EAC) is a rare and aggressive subtype of cervical cancer which is not associated with human papillomavirus (HPV) infection but has poor prognosis because of its high invasiveness and resistance to chemoradiotherapy. The early and accurate diagnosis of G-EAC is challenging owing to its nonspecific symptoms and relatively normal cytological and histological manifestations.MethodsThe present study retrospectively analyzed the demographic and clinical characteristics, and cervical medical imaging features of 10 patients diagnosed with G-EAC at our institution during a five-year period. Postoperative cervical pathological features were examined, and followed-up information was collected. Novel ultrasonographic features of G-EAC were also summarized.ResultsThe patients aged 24–70 years (mean: 49.6 ± 11.6). Their clinical presentations included vaginal discharge (60%), irregular vaginal bleeding (40%), and contact bleeding (30%). Nine patients were HPV negative. Ultrasound examination revealed that there were two, three, two, and two cases of types I (multicystic), II (cystic-solid), III (solid), and IV (nearly normal cervix) G-EAC, respectively. There were four CA199 + and two CA125 + cases. Pathology examination confirmed two cases of synchronous mucinous metaplasia and neoplasia of the female genital tract and one case of Peutz–Jeghers syndrome and multiple gastrointestinal polyps. Ultrasonography for cystic lesions revealed a “cosmos sign”. Two patients with types I and II G-EAC exhibited vesicular echoes involving the lower uterine segment. In four cases, vesicular echoes were observed within the myometrium. This case series highlights the heterogeneous manifestations, complex imaging patterns, and multifaceted pathology of G-EACs.ConclusionsUltrasonography can facilitate the early diagnosis of G-EAC for relatively specific features, such as “cosmos signs” and “vesicular implantation signs.” The latter refers to ultrasound manifestations of multicystic or cystic-solid lesions of the cervix accompanied by vesicular lesion in the lower uterine segment and/or vesicular implantation in the myometrium.